2009
DOI: 10.2350/08-02-0424.1
|View full text |Cite
|
Sign up to set email alerts
|

Calretinin Immunohistochemistry versus Acetylcholinesterase Histochemistry in the Evaluation of Suction Rectal Biopsies for Hirschsprung Disease

Abstract: Diagnosis of Hirschsprung disease (HSCR) relies on histologic and/or histochemical staining of sections from suction rectal biopsies. Acetylcholinesterase histochemistry (AChE) facilitates diagnosis but is not universally employed, in part because it requires special tissue handling. Calretinin immunohistochemistry (IHC) may be a useful alternative, because loss of calretinin immunoreactive nerves reportedly correlates spatially with aganglionosis. We investigated the patterns of calretinin IHC in suction rect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
121
2
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(139 citation statements)
references
References 33 publications
12
121
2
4
Order By: Relevance
“…Of interest, recently Barshack et al 25 reported that calretinin immunostaining was absent in intrinsic nerve fibers in Hirschsprung colons, whereas it is identified in ganglion cells and intrinsic nerve fibers of nonHirschsprung patients. As a follow-up, Kapur et al 22 retrospectively applied calretinin immunostain to 14 Hirschsprung and 17 non-Hirschsprung patients, with staining results similar to the findings of Barshack et al 25 Further, this group compared the calretinin immunostain with the acetylcholinesterase stains performed at initial biopsy. They concluded that the calretinin immunohistochemical stain was superior to acetylcholinesterase histochemical stain in these evaluations.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Of interest, recently Barshack et al 25 reported that calretinin immunostaining was absent in intrinsic nerve fibers in Hirschsprung colons, whereas it is identified in ganglion cells and intrinsic nerve fibers of nonHirschsprung patients. As a follow-up, Kapur et al 22 retrospectively applied calretinin immunostain to 14 Hirschsprung and 17 non-Hirschsprung patients, with staining results similar to the findings of Barshack et al 25 Further, this group compared the calretinin immunostain with the acetylcholinesterase stains performed at initial biopsy. They concluded that the calretinin immunohistochemical stain was superior to acetylcholinesterase histochemical stain in these evaluations.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, the stains may be difficult to interpret, particularly in ambiguous cases. 3,4 The demands of interpretation of this stain are well documented with false positive, [4][5][6]8,9 false negative, [18][19][20][21][22] and equivocal 19,22 results.…”
Section: Discussionmentioning
confidence: 99%
“…21 Nerve cell bodies in both submucosa and myenteric ganglia of guinea pig 22,23 and in the human gastrointestinal tract are immunopositive for calretinin, a calcium-binding protein. 24 Recently, it has been suggested that calretinin might be more accurate than acetylcholinesterase in detecting aganglionosis 18 in a small series of rectal biopsy. Our study demonstrates for the first time in a large series of rectal suction biopsies that pathologists can diagnose all cases of HD with no false positives using the sole immunohistochemistry with calretinin antibody, and that the concordance between calretinin and the gold standard (ie, surgery for HD patients) is statistically excellent, whereas the concordance between the standard technique and the Gold standard is only good.…”
Section: Discussionmentioning
confidence: 99%
“…This binary pattern of interpretation (positive/negative) gives the technique distinctive ease and reproducibility, avoiding the need for repeated biopsies and delayed treatment. But because of the phenotypically heterogeneous nature of HD as provided by Kapur,18 the utility of calretinin immunohistochemistry, in particular in circumstances such as ultrashort segment HD or transitional zone assessments, remains to be determined, and calretinin immunohistochemistry should always be used in addition to limited hematoxylin and eosin sections. …”
Section: Discussionmentioning
confidence: 99%
“…Acetylcholinesterase histochemistry (AChE) aids diagnosis but has its pitfalls as it requires special handling of the tissue. 7 One study further added that a certain type of nerve cell bodies in submucosa and the myenteric ganglia of the gastrointestinal tract were seen to show immunopositivity for calretinin. 8 Latestly, it is reported that calretinin immunohistochemical staining is found to be superior to conventional acetylcholinesterase staining to confirm absence of ganglions.…”
Section: Introductionmentioning
confidence: 99%